A method for preparing a low-Pt catalyst using a non-precious metal catalyst as a carrier
By supporting Pt and CeO2 through redox reaction on non-precious metal catalysts, the problems of uneven metal distribution and low activity in low Pt catalysts are solved, and the high oxygen reduction activity and stability of the catalyst are achieved, and the cost is reduced.
Patent Information
- Application Number
- CN202110358739.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-01
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-04-01
AI Technical Summary
During the preparation process, existing low Pt catalysts have problems such as uneven metal distribution, low activity and agglomeration of Pt nanoparticles. The by-product H2O2 of the non-precious metal catalyst has strong oxidation properties, which affects the stability of the catalyst.
By combining the non-precious metal catalyst, Pt and CeO2, the redox reaction of Pt and CeO2 is used to directly support Pt and CeO2 on the non-precious metal catalyst to achieve uniform distribution and avoid agglomeration caused by high temperature treatment.
This method allows Pt and CeO2 to be evenly distributed on the catalyst support, improves the oxygen reduction activity and stability of the catalyst, reduces costs, and effectively alleviates the oxidation of H2O2.
Smart Images

Figure CN115188973B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of non-precious metal catalysts for proton exchange membrane fuel cells, and specifically discloses a method for preparing a low-Pt catalyst using the non-precious metal catalyst as a carrier. Background Art
[0002] Pt-based catalysts are usually prepared by three methods: using reducing agents such as sodium borohydride and ascorbic acid to directly load on carbon carriers through liquid phase reduction reactions; loading Pt nanoparticles on carbon carriers through magnetron sputtering and physical vapor deposition; or fully impregnating Pt salts on carbon carriers and then performing heat treatment under a reducing atmosphere to achieve Pt loading on carbon carriers. Traditional carbon carriers have no active sites and only serve to load Pt nanoparticles. In addition, the dispersion of Pt in Pt-based catalysts prepared by traditional methods is difficult to control, and Pt agglomerates are very likely to appear.
[0003] In order to further reduce the amount of Pt in fuel cells, combining non-precious metal catalysts with Pt-based catalysts is a more effective solution. Patent CN202011181023.9 invented a low-platinum / non-platinum composite catalyst, which uses alcohol as a solvent, alkaline reaction medium ligand replacement combined with reducing gas to calcine and reduce the platinum precursor to form the nanoparticle catalyst. However, Pt nanoparticles are prone to agglomeration during the calcination process, which ultimately leads to a decrease in catalyst activity. Patent CN201810319971.0 invented a low-Pt-loaded fuel cell catalyst using MOF as a template, dispersing cobalt nitrate, 2-aminoterephthalic acid and triethylenediamine in NN-dimethylformamide to form a MOF precursor mixed solution; preparing MOF by solvothermal method, washing, drying to obtain MOF powder; adding to sodium chloroplatinate or chloroplatinic acid solution, stirring and dissolving, standing, washing, and drying; high-temperature treatment and acid washing under an inert atmosphere, and finally centrifugation washing, drying, and grinding the product. This method has a complicated process and high-temperature treatment easily causes agglomeration of Pt nanoparticles.
[0004] The low-Pt catalyst prepared in the above method has problems such as uneven metal distribution and low activity. In addition, the ORR byproduct H2O2 of the non-precious metal catalyst has strong oxidizing properties, which will cause chemical oxidation of the catalyst and key battery materials. Summary of the invention
[0005] The present invention combines a non-precious metal catalyst, Pt and CeO2 to obtain a low-Pt catalyst. The catalyst directly supports Pt and CeO2 on the non-precious metal catalyst through the redox reaction of Pt salt and Ce salt. The process does not introduce other impurities and does not require high temperature to make Pt and CeO2 evenly distributed on the non-precious metal catalyst carrier. In the catalyst of this structure, the synergistic effect of the non-precious metal carrier and N and Pt in the non-precious carrier effectively improves the oxygen reduction activity of the catalyst. In addition, the addition of CeO2 can improve the dispersibility of Pt and can also alleviate the attenuation problem caused by the oxidation of H2O2, a byproduct of the non-precious metal catalyst. Experimental results show that the catalyst has good oxygen reduction activity and stability.
[0006] The present invention specifically provides a method for preparing a low-Pt catalyst using a non-precious metal catalyst as a carrier, the preparation method comprising the following steps:
[0007] (1) preparing an MNC type non-precious metal catalyst, wherein M is a non-precious metal and the N content is greater than 0.5 wt %;
[0008] (2) The synthesized non-precious metal catalyst is used as a carrier and dispersed in a solvent, and then a Ce salt is added. A Pt salt is added under the protection of an inert gas, and the molar ratio of the Ce salt to the Pt salt is 10:1-1:1. The pH of the solvent is adjusted to 7-14, and the Pt salt and the Ce salt undergo a redox reaction. After the reaction, Pt and CeO2 are loaded on the carrier. Finally, the product is centrifuged, vacuum dried, and ground for later use to obtain the catalyst PtCeO2@MNC.
[0009] Based on the above technical solution, preferably, the MNC type non-precious metal catalyst is obtained by mixing a non-precious metal source, a carbon source, and a nitrogen source and pyrolyzing them (ie, a traditional doping method) or by pyrolyzing a metal organic framework compound.
[0010] Based on the above technical scheme, preferably, the non-metallic source includes one or more of Fe source, Co source, Ni source, and Mn source; the Fe source is one or more of ferric chloride, ferric sulfate, ferric oxalate, and ferric nitrate; the Co source is one or more of cobalt chloride, cobalt sulfate, cobalt oxalate, and cobalt nitrate; the Ni source is one or more of nickel chloride, nickel sulfate, nickel oxalate, and nickel nitrate; the Mn source is one or more of manganese chloride, manganese sulfate, manganese oxalate, and manganese nitrate. The carbon source is one or more of carbon black, activated carbon, carbon tube, graphene, polyacrylonitrile, and polyacrylic acid. The nitrogen source is one or more of dimethylimidazole, ethylenediamine, hexamethylenediamine, phthalic acid, phthalic acid imidazole, or dimethylimidazole.
[0011] Based on the above technical scheme, preferably, the metal organic framework compound precursor can be one or more of Fe-ZIF8, FeCo-ZIF8, ZIF67, MIL-101, etc.
[0012] Based on the above technical scheme, preferably, the pyrolysis conditions of non-metallic sources, carbon sources, nitrogen sources and metal organic framework compounds are: pyrolysis temperature is 500-1300°C, pyrolysis time is 0.5-3h, and pyrolysis atmosphere is one of nitrogen, argon or ammonia.
[0013] Based on the above technical solution, preferably, in the PtCeO2@MNC catalyst, the Pt loading is 0.5-25wt%, more preferably 5-10wt%; the CeO2 loading is 1-50wt%; more preferably 15-25%.
[0014] Based on the above technical solution, preferably, the solvent is one of ethanol, methanol, water or N-dimethylformamide (DMF).
[0015] Based on the above technical scheme, preferably, the Ce salt is one or more of cerium nitrate (hydrated), cerium chloride (hydrated), cerium sulfate (hydrated), cerium acetate (hydrated), and cerium oxalate (hydrated). The Pt salt is one or more of potassium chloroplatinite (hydrated), sodium tetrachloroplatinate (hydrated), dinitrosyl platinous acid sulfate, and dinitroso diamine platinum. Wherein, the amount of the non-precious metal catalyst added to the solvent is 0.1 mg L -1 -2.5mg L -1 The concentration of Pt salt is 0.25 mmol L -1 -10mmol L -1 The pH range of the reaction solvent can be adjusted to 7-14 using NaOH, KOH, etc.
[0016] Based on the above technical solution, preferably, the inert gas is one of nitrogen, argon, helium, neon, argon, krypton, xenon and radon.
[0017] Based on the above technical solution, preferably, the reaction temperature of the Pt salt and the Ce salt is 20-100°C, and the reaction time is 1-10h;
[0018] Based on the above technical solution, preferably, the vacuum drying temperature is 20 to 90° C., and the drying time is 1 to 24 hours;
[0019] The catalyst prepared by the above method can better maintain the morphology of the carrier. If the carrier of the non-precious metal catalyst used is a rhombic dodecahedron, the catalyst after loading Pt and CeO2 can still better maintain the rhombic dodecahedron morphology. The Pt and CeO2 are evenly distributed at the atomic level on the surface of the carrier, that is, the Pt and CeO2 on the final catalyst surface are evenly distributed and dispersed, and no metal agglomeration occurs.
[0020] The present invention also provides an application of the above catalyst, wherein the catalyst is used as an ORR cathode catalyst in an acidic or alkaline fuel cell, and the catalyst acts as a cathode catalyst in a proton exchange membrane fuel cell to reduce oxygen.
[0021] The principle of the present invention is: Pt and CeO2 are directly loaded on a non-precious metal catalyst carrier by using a redox reaction between Pt salt and Ce salt. The morphology of the catalyst can still maintain the previous morphology of the carrier. In addition, Pt and CeO2 can be evenly distributed at the atomic level on the surface of the carrier, and there will be no metal agglomeration. This scheme combines non-precious metal catalysts with Pt-based catalysts, effectively reducing costs while improving catalyst activity; in addition, the presence of CeO2 can effectively alleviate the chemical oxidation of H2O2, a byproduct of non-precious metal catalysts, and help improve the stability of the catalyst; finally, the catalyst preparation method is simple and can be used to load Pt and CeO2 on various forms of non-precious metal catalysts.
[0022] Beneficial Effects
[0023] (1) The present invention is applicable to various forms of non-precious metal catalysts. In addition, the catalyst after loading Pt and CeO2 can still maintain the original morphology of the non-precious metal catalyst. By adjusting the ratio of Pt salt and Ce salt in the reactant, Pt and CeO2 can be evenly distributed on the carrier without the presence of metal agglomeration. This structure can promote the interaction between N, CeO2 and Pt in the non-precious metal catalyst carrier, and then adjust the electron distribution in Pt, thereby improving the ORR activity. In addition, the reaction conditions of Pt salt and Ce salt are mild, and no subsequent high-temperature pyrolysis process is required, so that Pt and CeO2 are highly dispersed. The improvement of Pt dispersion can improve the utilization rate of Pt, thereby reducing costs.
[0024] (2) The presence of CeO2 in the catalyst of the present invention has multiple effects. First, CeO2 can improve the dispersibility of Pt. In addition, CeO2 has abundant oxygen vacancies, which can effectively alleviate the oxidation of Pt while improving the ORR activity of Pt. Finally, CeO2 can in situ quench the H2O2 released during the ORR reaction of the non-precious metal catalyst.
[0025] (3) The catalyst prepared by the present invention has multiple active sites. First, the loading reaction of Pt and CeO2 is a weakly alkaline environment, which will not affect the active sites in the non-precious metal catalyst; in addition, the interaction between N and Pt in the non-precious metal catalyst carrier can adjust the electron distribution in Pt, thereby improving the ORR activity of Pt.
[0026] (4) The synthesis process is simple and easy, the atomic utilization rate of the catalyst is greatly improved, and the mass specific activity is 2-6 times that of the traditional Pt / C catalyst. This catalyst has great application prospects in effectively reducing the cost of proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a performance comparison chart of the PtCeO2@Fe-NC catalyst prepared in Example 1 and the Pt / C catalyst in Comparative Example 1.
[0028] Figure 2 This is a comparison chart of the CV curves of the PtCeO2@Fe-NC catalyst prepared in Example 1 and the Pt / C catalyst in Comparative Example 1.
[0029] Figure 3 This is the initial morphology of the Fe-NC support prepared in Example 1.
[0030] Figure 4 This is the morphology of the PtCeO2@Fe-NC catalyst prepared in Example 1 (after Pt and CeO2 are loaded on the Fe-NC carrier).
[0031] Figure 5 1 is the distribution diagram of each element of the PtCeO2@Fe-NC catalyst prepared in Example 1, wherein the second figure is the HADDEF (high-angle annular dark field image) of the catalyst.
[0032] Figure 6 This is a comparison chart of the changes in H2O2 release before and after attenuation of the PtCeO2@Fe-NC catalyst prepared in Example 1 and the Fe-NC catalyst in Comparative Example 3.
[0033] Figure 7 This is a performance comparison chart of the PtCeO2@Co-NC catalyst prepared in Example 2 and the Pt / C catalyst in Comparative Example 2.
[0034] Figure 8 This is the TEM image of Comparative Example 4.
[0035] Fig. 9 This is the TEM image of Comparative Example 5.
[0036] Fig.10Comparison of the ring currents of the PtCeO2@Fe-NC catalyst prepared in Example 1 and the Pt@Fe-NC catalyst prepared in Comparative Example 6.
[0037] Fig.11 This is a performance comparison chart of the PtCeO2@XC-72 catalyst prepared in Comparative Example 7 and the PtCeO2@Fe-NC catalyst prepared in Example 1. DETAILED DESCRIPTION
[0038] Example 1
[0039] Preparation of Fe-NC catalyst carrier: Weigh 2.2g Zn(NO3)2·6H2O and 0.2g Fe(NO3)3·9H2O and dissolve them in 100ml anhydrous methanol, mix them ultrasonically for 20min, and record them as solution A. Weigh 2.5g 2-methylimidazole and dissolve it in 20ml anhydrous methanol, stir for 20min, and record it as solution B. Then, mix solutions A and B evenly and place them in a 60℃ oil bath to react for 24h. After the reaction is completed, wash it with anhydrous ethanol twice and dry it in a vacuum oven (60℃) for 12h. The dried white precursor is pyrolyzed at 1100℃ in a nitrogen atmosphere for 1h (heating rate 5℃ min -1 ), and finally the obtained catalyst product is fully ground and recorded as Fe-NC catalyst carrier.
[0040] Loading Pt and CeO2 on Fe-NC catalyst carrier: First, 100 mg of Fe-NC catalyst carrier was dispersed in 80 ml of ethanol solution, 2 mmol of cerium chloride (CeCl3.7H2O) was added, and the mixture was placed in a 20°C oil bath with stirring and N2 passed for 30 min. The pH was adjusted to 7, and then 0.2 mmol of dinitrosodiammineplatinum (the ratio of Ce salt to Pt salt was 10:1) was added. Gas was continuously passed during the reaction. The mixture was taken out after 1 h of reaction and cooled to room temperature. The synthesized catalyst was centrifuged, washed with deionized water and anhydrous ethanol, and placed in a vacuum oven at 20°C for 24 h to obtain PtCeO2@Fe-NC catalyst.
[0041] Figure 1 The performance comparison diagram of the PtCeO2@Fe-NC catalyst prepared in Example 1 and the Pt / C catalyst in Comparative Example 1 is shown in the figure. It can be seen from the figure that the non-precious metal catalyst carrier in Example 1 also has a certain activity. In addition, CeO2 can not only improve the dispersibility of Pt, but also interact with Pt to promote O2 adsorption, thereby facilitating the breaking of the OO bond; the abundant oxygen vacancies can increase the oxygen storage capacity of the catalyst, so that more Pt can contact O2. Therefore, the activity of this catalyst is significantly higher than that of the Pt / C catalyst.
[0042] Figure 2 The figure is a comparison of the CV curves of the PtCeO2@Fe-NC catalyst prepared in Example 1 and the Pt / C catalyst in Comparative Example 1. Compared with the catalyst prepared by the traditional method, the carrier in Example 1 uses a non-precious metal catalyst, which has a higher specific surface area, so the double layer region of the CV curve is higher.
[0043] Figure 3 This is the initial morphology of the Fe-NC support prepared in Example 1. Figure 4 The morphology of the PtCeO2@Fe-NC catalyst shows that after being loaded with Pt and CeO2, the overall morphology of the catalyst still maintains the morphology of a rhombic regular dodecahedron, indicating that the catalyst finally prepared by the method of the present invention can better maintain its original morphology.
[0044] Figure 5 The figure shows the distribution of elements of the PtCeO2@Fe-NC catalyst prepared in Example 1, where the second figure is the HADDEF (high-angle annular dark field image) of the catalyst. It can be seen intuitively that the Fe, N, and C elements are evenly distributed inside the catalyst, while Pt and Ce are evenly distributed in the outer layer of the catalyst, further proving that Pt and CeO2 are successfully and evenly coated on the outer layer of the Fe-NC catalyst. In addition, it can be seen from the figure that Pt and CeO2 are evenly distributed and dispersed on the catalyst surface, without metal agglomeration, and are evenly distributed at the atomic level.
[0045] Example 2
[0046] Preparation of Co-NC catalyst carrier: Weigh 2g Zn(NO3)2·6H2O and 0.2g Co(NO3)3·6H2O and dissolve them in 100ml anhydrous methanol, mix them ultrasonically for 20min, and record them as solution A. Weigh 2g 2-methylimidazole and dissolve it in 20ml anhydrous methanol, stir for 20min, and record it as solution B. Then, mix solutions A and B evenly and place them in a 60℃ oil bath to react for 24h. After the reaction is completed, wash it with anhydrous ethanol twice and dry it in a vacuum oven (60℃) for 12h. The dried white precursor is pyrolyzed at 900℃ in an argon atmosphere for 1h (heating rate 5℃min -1 ), and finally the obtained catalyst product was fully ground and recorded as Co-NC catalyst support.
[0047] Loading Pt and CeO2 on Co-NC catalyst carrier: First, 100 mg of Co-NC catalyst carrier was dispersed in 80 ml of aqueous solution, and 0.5 mmol of cerium acetate (CH3CO2)3Ce.6H2O was added. Then, it was placed in a 100°C oil bath, stirred and passed through Ar for 30 min, and the pH was adjusted to 14. Then, 0.5 mmol of potassium chloroplatinite was added (the ratio of Ce salt to Pt salt was 1:1). Gas was continuously passed during the reaction. After 10 h of reaction, it was taken out and cooled to room temperature. The synthesized catalyst was centrifuged, washed with deionized water and anhydrous ethanol, and placed in a vacuum oven at 100°C for 1 h.
[0048] Figure 7 The performance comparison diagram of the PtCeO2@Co-NC catalyst prepared in Example 2 and the Pt / C catalyst in Comparative Example 2 is shown. The experimental results show that due to the activity of the non-precious metal catalyst carrier and the promotion effect of CeO2, the activity of the catalyst in Example 2 is significantly higher than that of the Pt / C catalyst with traditional carbon black as the carrier.
[0049] Comparative Example 1
[0050] Preparation of Pt / C catalyst: Disperse 100 mg XC-72 evenly in 80 ml EG. After passing N2 into the dispersion for 30 minutes, place the flask in a 60°C oil bath and preheat for 10 minutes. Dissolve NaBH4 in a small amount of deionized water and add it to the dispersion. Subsequently, add 0.2 mmol H2PtCl6 to the dispersion and continue to react for 30 minutes under stirring at 60°C (maintain an inert atmosphere). After the reaction is completed, the catalyst is centrifuged and washed with deionized water / ethanol. After washing, vacuum dry at 60°C for 12 hours to obtain the product.
[0051] Comparative Example 2
[0052] Preparation of Pt / C catalyst: First, add 0.5mmol of acetylacetonate platinum (Pt(acac)2), 100mg of benzoic acid, 50mg of hexadecyltrimethyl bromide and 20mL of N,N-dimethylformamide (DMF) into a 25mL flask, add 100mg of XC-72, stir and ultrasonicate to make it dispersed evenly. Then transfer the dispersion into a 25mL reactor, seal it and react at 180℃ for 12h. After the reactor is cooled to room temperature, the product is centrifuged and washed with anhydrous ethanol and deionized water, and then placed in a vacuum oven at 60℃ for one night.
[0053] Comparative Example 3
[0054] Preparation of Fe-NC catalyst: Weigh 2.2g Zn(NO3)2·6H2O and 0.2g Fe(NO3)3·9H2O and dissolve them in 100ml anhydrous methanol, mix them ultrasonically for 20min, and record it as solution A. Weigh 2.5g 2-methylimidazole and dissolve it in 20ml anhydrous methanol, stir it for 20min, and record it as solution B. Then, mix the two solutions A and B evenly and place them in a 60℃ oil bath to react for 24h. After the reaction is completed, wash it with anhydrous ethanol twice and dry it in a vacuum oven (60℃) for 12h. The dried white precursor is pyrolyzed at 1100℃ in a nitrogen atmosphere for 1h (heating rate 5℃ min -1 ), and finally the obtained catalyst product was fully ground and recorded as Fe-NC catalyst.
[0055] Comparative Example 4
[0056] The Fe-NC catalyst prepared in Example 1 was used as a carrier, except that the addition ratio of Ce salt to Pt salt was adjusted to 11:1, so as to compare the effect of the addition ratio of Pt salt to Ce salt on the metal distribution.
[0057] Preparation of Fe-NC catalyst carrier: Weigh 2.2g Zn(NO3)2·6H2O and 0.2g Fe(NO3)3·9H2O and dissolve them in 100ml anhydrous methanol, mix them ultrasonically for 20min, and record them as solution A. Weigh 2.5g 2-methylimidazole and dissolve it in 20ml anhydrous methanol, stir for 20min, and record it as solution B. Then, mix solutions A and B evenly and place them in a 60℃ oil bath to react for 24h. After the reaction is completed, wash it with anhydrous ethanol twice and dry it in a vacuum oven (60℃) for 12h. The dried white precursor is pyrolyzed at 1100℃ in a nitrogen atmosphere for 1h (heating rate 5℃ min -1 ), and finally the obtained catalyst product is fully ground and recorded as Fe-NC catalyst carrier.
[0058] Loading Pt and CeO2 on Fe-NC catalyst carrier: First, 100 mg of Fe-NC catalyst carrier was dispersed in 80 ml of ethanol solution, 2 mmol of cerium chloride (CeCl3.7H2O) was added, and the mixture was placed in a 20°C oil bath, stirred and passed through N2 for 30 min, and the pH was adjusted to 7. Subsequently, 2.2 mmol of dinitrosodiammineplatinum (the ratio of Ce salt to Pt salt was 11:1) was added, and gas was continuously passed through during the reaction. The mixture was taken out after 1 h of reaction and cooled to room temperature. The synthesized catalyst was centrifuged, washed with deionized water and anhydrous ethanol, and placed in a vacuum oven at 20°C for 24 h to obtain PtCeO2@Fe-NC catalyst.
[0059] Figure 8 TEM image of Comparative Example 4. Figure 5 (PtCeO2@Fe-NC catalyst prepared in Example 1) and Figure 7 It can be found that metal agglomeration is likely to occur when the ratio of Ce salt to Pt salt in the reaction solution is too high.
[0060] Comparative Example 5
[0061] The Co-NC catalyst prepared in Example 2 was used as a carrier, except that the addition ratio of Ce salt to Pt salt was adjusted to 0.5:1, so as to compare the effect of the addition ratio of Pt salt to Ce salt on the metal distribution.
[0062] Preparation of Co-NC catalyst carrier: Weigh 2g Zn(NO3)2·6H2O and 0.2g Co(NO3)3·6H2O and dissolve them in 100ml anhydrous methanol, mix them ultrasonically for 20min, and record them as solution A. Weigh 2g 2-methylimidazole and dissolve it in 20ml anhydrous methanol, stir for 20min, and record it as solution B. Then, mix the A and B solutions evenly and place them in a 60℃ oil bath to react for 24h. After the reaction is completed, wash them with anhydrous ethanol twice and dry them in a vacuum oven (60℃) for 12h. The dried white precursor is pyrolyzed at 900℃ in an argon atmosphere for 1h (heating rate 5℃ min -1 ), and finally the obtained catalyst product was fully ground and recorded as Co-NC catalyst support.
[0063] Loading Pt and CeO2 on Co-NC catalyst carrier: First, 100 mg of Co-NC catalyst carrier was dispersed in 80 ml of aqueous solution, and 0.25 mmol of cerium acetate (CH3CO2)3Ce.6H2O was added. Then, it was placed in a 100°C oil bath, stirred and passed through Ar for 30 min, and the pH was adjusted to 14. Then, 0.5 mmol of potassium chloroplatinite was added (the ratio of Ce salt to Pt salt was 0.5:1). Gas was continuously passed during the reaction. After 10 h of reaction, it was taken out and cooled to room temperature. The synthesized catalyst was centrifuged, washed with deionized water and anhydrous ethanol, and placed in a vacuum oven at 100°C for 1 h.
[0064] Fig. 9 TEM image of Comparative Example 5. Figure 6 (PtCeO2@Co-NC catalyst prepared in Example 2) and Figure 8 It can be found that metal agglomeration is also likely to occur when the ratio of Ce salt to Pt salt in the reaction solution is too low.
[0065] Comparative Example 6
[0066] The Fe-NC catalyst was prepared according to the method in Example 1, and the same content of Pt was loaded on the Fe-NC carrier by a reduction method to prepare a Pt@Fe-NC catalyst.
[0067] The specific method is as follows: 0.2mmol acetylacetonate platinum (Pt(acac)2), 50mg benzoic acid, 25mg hexadecyl trimethyl bromide and 10mL N, N-dimethylformamide (DMF) are added to a 25mL flask, 100mg Fe-NC catalyst carrier is added, and the dispersion is stirred and ultrasonically dispersed evenly. Then the dispersion is transferred to a 25mL reactor, sealed and reacted at 180℃ for 12h. After the reactor is cooled to room temperature, the product is centrifuged and washed with anhydrous ethanol and deionized water, and then placed in a vacuum oven at 60℃ for one night.
[0068] Fig.10 By comparing the ring currents of the PtCeO2@Fe-NC catalyst prepared in Example 1 and the Pt@Fe-NC catalyst prepared in Comparative Example 6, it can be found that only under the condition of Pt loading, the release amount of H2O2 is still high. This result also shows that the addition of CeO2 can effectively reduce the release amount of H2O2.
[0069] Comparative Example 7
[0070] Loading Pt and CeO2 on the traditional carrier XC-72: First, 100 mg of Fe-NC catalyst carrier was dispersed in 80 ml of ethanol solution, 2 mmol of cerium chloride (CeCl3.7H2O) was added, and the mixture was placed in a 20°C oil bath with stirring and N2 passed for 30 min. The pH was adjusted to 7, and then 0.2 mmol of dinitrosodiammineplatinum (the ratio of Ce salt to Pt salt was 10:1) was added. Gas was continuously passed during the reaction. The mixture was taken out after 1 h of reaction and cooled to room temperature. The synthesized catalyst was centrifuged, washed with deionized water and anhydrous ethanol, and placed in a vacuum oven at 20°C for 24 h to obtain PtCeO2@XC-72 catalyst.
[0071] Fig.11 This is a LSV comparison diagram of PtCeO2@Fe-NC in Example 1 and PtCeO2@XC-72 in Comparative Example 7. It can be seen that when the carrier is XC-72, the carrier is inactive. In addition, due to the lack of interaction between N in MNC and CeO2 and Pt, the ORR is significantly reduced.
Claims
1. A method for preparing a low-Pt catalyst using a non-precious metal catalyst as a carrier, characterized in that: The preparation method comprises the following steps: (1) preparing an MNC type non-precious metal catalyst, wherein M is a non-precious metal and the N content is greater than 0.5 wt %; (2) The synthesized non-precious metal catalyst is used as a carrier and dispersed in a solvent, and then a Ce salt is added. A Pt salt is added under the protection of an inert gas, and the molar ratio of the Ce salt to the Pt salt is 10:1-1:
1. The pH of the solvent is adjusted to 7-14, and the Pt salt and the Ce salt undergo a redox reaction. After the reaction, Pt and CeO2 are loaded on the carrier. Finally, the product is centrifuged, vacuum dried, and ground for later use to obtain the catalyst PtCeO2@MNC.
2. The preparation method according to claim 1, characterized in that: The reaction temperature of the Pt salt and the Ce salt is 20-100°C, and the reaction time is 1-10 hours; the vacuum drying temperature is 20-90°C, and the drying time is 1-24 hours; the inert gas is one of nitrogen, argon, helium, neon, argon, krypton, xenon, and radon; the solvent is one of ethanol, methanol, water, or dimethylformamide (DMF).
3. The preparation method according to claim 1, characterized in that: The Ce salt is one or more of cerium nitrate, cerium chloride, cerium sulfate, cerium acetate, and cerium oxalate; the Pt salt is one or more of potassium chloroplatinite, sodium tetrachloroplatinate, dinitrosylplatinous acid sulfate, and dinitrosodiammineplatinum; wherein the amount of the non-precious metal catalyst added to the solvent is 0.1 mg L -1 -2.5mg L -1 ; The concentration of Pt salt is 0.25mmol L -1 -10mmol L -1 ; The reagent used to adjust the pH of the solvent is NaOH or KOH.
4. The preparation method according to claim 1, characterized in that: In the PtCeO2@MNC catalyst, the loading amount of Pt is 0.5-25wt%; the loading amount of CeO2 is 1-50wt%.
5. The preparation method according to claim 1, characterized in that: The MNC type non-precious metal catalyst is obtained by mixing a non-precious metal source, a carbon source and a nitrogen source and then pyrolyzing them, or by pyrolyzing a metal organic framework compound.
6. The preparation method according to claim 5, characterized in that: The non-precious metal source includes one or more of Fe source, Co source, Ni source and Mn source; the Fe source is one or more of ferric chloride, ferric sulfate, ferric oxalate and ferric nitrate; the Co source is one or more of cobalt chloride, cobalt sulfate, cobalt oxalate and cobalt nitrate; the Ni source is one or more of nickel chloride, nickel sulfate, nickel oxalate and nickel nitrate; the Mn source is one or more of manganese chloride, manganese sulfate, manganese oxalate and manganese nitrate; the carbon source is one or more of carbon black, activated carbon, carbon tube, graphene, polyacrylonitrile and polyacrylic acid; the nitrogen source is one or more of dimethylimidazole, ethylenediamine, hexamethylenediamine, phthalic acid, phthalic acid imidazole or dimethylimidazole; the metal organic framework compound precursor is one or more of Fe-ZIF8, FeCo-ZIF8, ZIF67 and MIL-101.
7. The preparation method according to claim 5, characterized in that: The pyrolysis conditions of non-precious metal sources, carbon sources, nitrogen sources and metal organic framework compounds are as follows: pyrolysis temperature is 500-1300°C, pyrolysis time is 0.5-3h, and pyrolysis atmosphere is one of nitrogen, argon or ammonia.
8. A catalyst prepared by the method according to any one of claims 1 to 7, characterized in that: The catalyst maintains the morphology of the carrier, and the Pt and CeO2 are evenly distributed on the surface of the carrier at the atomic level.
9. The catalyst according to claim 8, characterized in that The carrier of the non-precious metal catalyst is a rhombic dodecahedron, and the catalyst after loading Pt and CeO2 maintains a rhombic dodecahedron shape.
10. Use of the catalyst according to claim 8, characterized in that: The catalyst is used as a fuel cell cathode catalyst in an acidic or alkaline fuel cell.
Citation Information
Patent Citations
Method for preparing low Pt loading capacity type fuel battery catalyst by utilizing MOF as template
CN108428906A
Low-platinum / non-platinum composite catalyst and preparation method thereof
CN112186207A
Catalyst with low Pt loading capacity as well as preparation method and application thereof
CN114284516A
Composite catalyst for alkaline fuel cell, preparation method of composite catalyst and alkaline fuel cell
CN115084543A